Developmental organization of central neurons in the adult Drosophila ventral nervous system. - Shepherd, D.; Sahota, V.; Court, R.; Williams, D.W.; Truman, J.W. (Journal of Comparative Neurology, 2019)
We have used MARCM to reveal the adult morphology of the post embryonically produced neurons in the thoracic neuromeres of the Drosophila VNS. The work builds on previous studies of the origins of the adult VNS neurons to describe the clonal organization of the adult VNS. We present data for 58 of 66 postembryonic thoracic lineages, excluding the motor neuron producing lineages (15 and 24) which have been described elsewhere. MARCM labels entire lineages but where both A and B hemilineages survive (e.g., lineages 19, 12, 13, 6, 1, 3, 8, and 11), the two hemilineages can be discriminated and we have described each hemilineage separately. Hemilineage morphology is described in relation to the known functional domains of the VNS neuropil and based on the anatomy we are able to assign broad functional roles for each hemilineage. The data show that in a thoracic hemineuromere, 16 hemilineages are primarily involved in controlling leg movements and walking, 9 are involved in the control of wing movements, and 10 interface between both leg and wing control. The data provide a baseline of understanding of the functional organization of the adult Drosophila VNS. By understanding the morphological organization of these neurons, we can begin to define and test the rules by which neuronal circuits are assembled during development and understand the functional logic and evolution of neuronal networks.